Aberrant regulation of RNA methylation during spermatogenesis. Issue 1 (1st December 2020) - Zhong, Dandan; Chen, Mengjie; Zhang, Lei; Chen, Hong; Shi, Deshun; Liu, Qingyou; Li, Hui
Abstract: Natural modifications of cellular RNA include various chemical modifications, such as N6 ‐methyladenosine (m 6 A), which enable the orderly metabolism and function of RNA structural diversity, thereby affecting gene expression. Spermatogenesis is a complex differentiating developmental process, which includes the proliferation of spermatogonial stem cells, spermatocyte meiosis and sperm maturation. Emerging evidence has shown that RNA methylation can influence RNA splicing, exportation and translation, which are controlled in the male germline in order to ensure coordinated gene expression. In this review, we summarize the typical characteristics of different types of RNA methylation during the process of spermatogenesis. In particular, we emphasize the functions of the RNA methylation effectors during the male germ cell development.